The CSB chromatin remodeler and CTCF architectural protein cooperate in response to oxidative stress - Lake, Robert J. (Nucleic Acids Res, 2016)
Cockayne syndrome is a premature aging disease associated with numerous developmental and neurological abnormalities, and elevated levels of reactive oxygen species have been found in cells derived from Cockayne syndrome patients. The majority of Cockayne syndrome cases contain mutations in the ATP-dependent chromatin remodeler CSB; however, how CSB protects cells from oxidative stress remains largely unclear. Here, we demonstrate that oxidative stress alters the genomic occupancy of the CSB protein and increases CSB occupancy at promoters. Additionally, we found that the long-range chromatin-structure regulator CTCF plays a pivotal role in regulating sites of genomic CSB occupancy upon oxidative stress. We show that CSB directly interacts with CTCF in vitro and that oxidative stress enhances the CSB-CTCF interaction in cells. Reciprocally, we demonstrate that CSB facilitates CTCF-DNA interactions in vitro and regulates CTCF-chromatin interactions in oxidatively stressed cells. Together, our results indicate that CSB and CTCF can regulate each other's chromatin association, thereby modulating chromatin structure and coordinating gene expression in response to oxidative stress.